PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN REMAJA PUTRI TENTANG SADARI DI SMAN 1 KUALA TUNGKAL: THE EFFECT OF HEALTH EDUCATION TOWARD KNOWLEDGE OF YOUNG WOMEN ABOUT SADARI AT SMAN I KUALA TUNGKAL - Salvita Fitrianti, Juliandini Haryani (Jurnal Psikologi Jambi, 2018)
INTRODUCTION According WHO, breast cancer incident increased from 12,7 million to 14,7 million cases. Cancer became the cause of death number two after cardovaskular disease. Estimated in 2030 incidence of cancer increases until 26 million cases and 17 million died of cancer. Breast cancer still have a great possibility to be cured if discovered while still at an earlystage or earlier.The simplest and cheapest way for early detection of breast lumps themselves (SADARI). This study aimed to determine the effect of health education toward knowledge of young women about SADARI at SMAN I Kuala Tungkal. METHOD This is a quantitative research by using pre-experiments pre-test and post-test by using one group pre and posttest design. The collecting of data used questionnaire. Populations were 507 students and samples were 20 respondents by using proportional random sampling. It analyzed as univariate and and bivariate by using dependent T-test. RESULT The findings indicated that there is the effect of health education toward knowledge of yaoung women about SADARI at SMAN I Kuala Tungkal with p-value 0.000 (p-value < 0,05) CONCLUSION AND RECOMMENDATION It is expected that public health office Tanjung Jabung Barat regency can conduct health education regularly and periodically about importance of SADARI on young women who cooperate with the public health center Tanjung Jabung Barat by using additional media such as phantom, leaflet and others. Keyword : SADARI, Teenagers, Health Education